Efficacy and toxicity of reduced vs. standard dose pegylated asparaginase in adults with Philadelphia chromosome-negative acute lymphoblastic leukemia. Issue 3 (23rd February 2020) - Derman, Benjamin A.; Streck, Mitchell; Wynne, Joseph; Christ, Trevor N.; Curran, Emily; Stock, Wendy; Knoebel, Randall W.
Abstract: Incorporation of asparaginase (ASNase) and pegylated asparaginase (PEG-ASP) into pediatric-inspired regimens for adults with acute lymphoblastic leukemia (ALL) has led to improved treatment outcomes albeit with increased toxicities. This study compared the efficacy and safety of the Children's Oncology Group standard PEG-ASP (SD) dosing (>1000, median 2500 IU/m 2 /dose) in adult Philadelphia chromosome-negative ALL patients receiving multiagent chemotherapy vs reduced dose PEG-ASP (RED) (≤1000, median 500 IU/m 2 /dose) during induction. 51 patients were included, 26 in RED and 25 in SD (median age 49 vs 37 years, p = .027). Median day 7 ASNase activity level for RED was 0.16 IU/mL. All 11 patients who received PEG-ASP 1000 IU/m 2 and 9/11 patients who received 500 IU/m 2 achieved an ASNase level ≥0.1 IU/mL. Patients receiving RED experienced fewer total grade 3/4 toxicities during induction compared to SD ( p = .02) while still attaining therapeutic ASNase levels. RED permits safer ASNase use in adults with ALL and should be tested in a larger cohort prospectively.